An Analysis of Politeness Strategies in the Animated Film “Soul” (2020) - David Andriano K Manurung; Kukuh Kartanagara; Briant Ahmad Alvyto (Universitas Sebelas Maret, 2025)
Politeness is not merely etiquette; it shapes how language conveys identity, emotion, and social connection. This study investigates politeness strategies in Soul (2020), a Pixar film that blends lighthearted storytelling with philosophical themes. Using Brown and Levinson’s (1987) framework comprising Bald on Record, Positive Politeness, Negative Politeness, and Off-Record strategies the study adopts a qualitative descriptive method. Data were collected from the film’s official script and cross-checked through multiple viewings for contextual accuracy. A total of 65 utterances were identified: 29 instances of positive politeness, 21 bald on record, 8 negative politeness, and 7 off-record strategies. These findings suggest the film prioritizes affirming, empathetic communication to navigate relationships and emotional transformation. The analysis demonstrates how politeness is used not only to manage social harmony, but also to express vulnerability and personal growth. Ultimately, the study highlights how animated dialogue can serve as a rich site for examining the interplay between language, meaning, and identity in animated storytelling.